Implementasi Merdeka Belajar - Kampus Merdeka (MBKM) di Universitas Muhammadiyah Sidoarjo - Putri, Iga Finalia; Astutik, Anita Puji (Asatiza: Jurnal Pendidikan, 2023)
Education is one way for humans to "survive" so they can adapt to the changing eras that are so fast. Therefore, a curriculum is needed that can facilitate the adaptation process. The concept of independent learning liberates education with free thinking and freedom in innovating. The purpose of this research is to find out the implementation of Freedom of Learning – Independent Campus (MBKM) at the Universitas Muhammadiyah Sidoarjo. A qualitative approach was chosen as the research design, the data was collected using the documentation technique. The analysis technique used is qualitative data analysis related to MBKM at the Universitas Muhammadiyah Sidoarjo. The results of the data analysis showed that Universitas Muhammadiyah Sidoarjo has adapted to the MBKM curriculum, the MBKM program that students are interested in, namely teaching assistants and industrial apprenticeships.